The Study of Lead Pollution in Street Dust and Drinking Water Along Arniko Rajmarg of Nepal - Shrestha, Reena Amatya; Kafle, Babi Kumar (Journal of Nepal Chemical Society, 2009)
Lead in street dust and drinking water along Arniko Rajmarg (ARM) of Nepal was analyzed. The concentration of lead is found high in the samples those were collected before monsoon and from heavy traffic regions. Keyword: lead, street dust, highways. DOI: 10.3126/jncs.v23i0.2105 Journal of Nepal Chemical Society, Vol. 23, 2008/2009 Page: 106-108